Enhancing Cybersecurity Information Sharing: A Secure and Decentralized Approach with Four-Node IPFS - Zaleha Fauziah; Novi Putri Anggraini; Yulia Putri Ayu Sanjaya; Tarisya Ramadhan (International Journal of Cyber ​​and IT Service Management (IJCITSM), 2023)
The act of sharing cybersecurity information plays a proactive and collaborative role in bolstering organizational security through the exchange of data using a centralized repository service. However, the real-world application of centralized services comes with certain risks. It leaves organizations vulnerable to distributed denial-of-service (DDoS) attacks, leading to system failures and creating a single point of failure. Additionally, it opens the door to man-in-the-middle (MITM) attacks, potentially altering or pilfering exchanged information. These threats undermine user confidence in the confidentiality, integrity, and availability of their data. This study presents a secure solution, the design of a Cybersecurity Information Sharing (CyberShare) system that employs a private interplanetary file system (IPFS) network as a decentralized information storage solution. Unlike centralized storage, which relies on a single node, the CyberShare system utilizes a four-node IPFS network interconnected with swarm keys for authentication. This design enables users to store and share information securely from sender to recipient, eliminating the need for reliance on a central server and reducing the server load. An analysis of the proposed CyberShare system demonstrates its capability to ensure the confidentiality, integrity, and availability of cybersecurity information. By enhancing information security, CyberShare systems empower organizations to securely share and utilize cybersecurity data.